Moisture and nutrient constraints to ecosystem processes in a forest regrowth stand in Eastern Amazonia, Brazil. - VASCONCELOS, S. S. (2006)
Changes in land-use and climate are likely to alter resource (e.g., moisture and nutrient) availability in tropical forest soils, but quantitative assessment of the role of resource constraints as regulators of ecosystem processes is rather limited. In this dissertation, moisture and nutrient availability were altered through dry-season irrigation and bi-weekly aboveground litter removal, respectively, to study how these resources control aboveground and belowground ecosystem processes in a forest regrowth stand in the Brazilian Amazon. Moisture availability strongly constrains soil respiration as indicated by the responses of soil carbon dioxide emissions to soil wet-up events and dry-season irrigation. Higher moisture availability in irrigated plots also increased leaf litter decomposition and slightly increased soil nitrous oxide and methane emissions, but did not alter monthly litterfall quantity and quality, and soil nitric oxide emission. Litter removal decreased carbon dioxide emissions and litterfall nitrogen concentration, but had no effects on litterfall quantity, and soil nitrogen oxides and methane emissions. Aboveground net primary productivity was constrained by moisture availability as indicated by the response of wood increment to interannual variation in dry season rainfall and to irrigation, suggesting decreased potential of carbon sequestration from forest regrowth under anticipated scenarios of reduced rainfall in Amazonia.